Mini Review: Rights and Obligations of Patients as Consumers of Health Services from An Islamic Perspective - Eva Nursoleha; Jihan Mahira Sitompul; Dhia Syifa; Nita Windi Lestari; Muhammad Zaini Fahmi (Solo International Collaboration and Publication of Social Sciences and Humanities, 2023)
Health is very important to improve the growth and development of the nation's life, and has an important role in shaping a healthy, just, and prosperous society. The synergy between the caring behaviour of medical servants and Islamic morality is expected to increase patient satisfaction with health services. In the context of medical services, the rights and obligations of patients as consumers are also regulated by law, where patients have the right to obtain information, protection, and compensation for errors in medical services. The purpose of this review article is to explain the application of Islamic law in health services, identify the rights and obligations of patients in the Islamic context, discuss the synergy of Islamic morality and health services, highlight the importance of balancing patient rights and obligations, provide an understanding of Muslim health consumer awareness, and encourage understanding of patient rights and obligations by the health law. The method of searching for scientific articles used as literature in this review through the website https://scholar.google.com using the keywords "patient rights and obligations"; "Islamic health services"; "patient rights in Islam"; "informed consent"; Health in Islamic perspective". The importance of the balance between patient rights and obligations, providing an understanding of health consumer awareness and encouraging understanding of patient rights by the health law.